The role of spring temperatures in the den exit of female brown bears with cubs in southwestern Europe - González-Bernardo, Enrique; Bombieri, Giulia; Delgado, María del Mar; Penteriani, Vincenzo (Ursus, 2020)
Hibernation represents the most refined adaptation of endothermic species to overcome unfavorable periods when food is scarce. Thus, hibernation should take place within specific time frames with respect to environmental factors. Flexibility in the timing of biological events is thus central to how well mammals can deal with varying climatic conditions. For brown bears (Ursus arctos), hibernation is not only a critical period that allows them to save vital energy reserves for times of food shortage, but also the period during which pregnant females give birth to cubs. Here, we analyzed the relationship between 74 den exit dates of females with cubs, recorded from 1995 to 2018 in the Cantabrian Mountains in northwestern Spain, with (1) average daily precipitation and (2) average maximum temperature during the 30 days before den exit, as well as with (3) the number of cubs. The bears exited from 1 April to 16 May, and the mean date was 28 April. Our results, which are consistent with the general latitudinal pattern of den emergence reported in other studies, suggested that in years with higher maximum temperatures, exit dates tended to be earlier, whereas the number of cubs and the average rainfall for the 30 days prior to den exit did not seem to determine the variation in den exit dates. Considering the relationship between spring temperatures and den exit dates of females with cubs, it is important to take into account the repercussions that current global warming may have on the reproduction of brown bears. Current trends of climate change might trigger earlier den exit dates than in the past, which may have negative consequences on the population dynamics of brown bear populations. For example, a mismatch between the chronology of hibernation and food availability might reduce cub survival and, consequently, the fitness of females. During this research, E.G.-B. was financially supported by a University Professorate Training (FPU) grant of the Spanish Ministry of Education and Professional Training ...